2016
DOI: 10.1016/j.medengphy.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring contractile dermal lymphatic activity following uniaxial mechanical loading

Abstract: a b s t r a c tIt is proposed that direct mechanical loading can impair dermal lymphatic function, contributing to the causal pathway of pressure ulcers. The present study aims to investigate the effects of loading on human dermal lymphatic vessels.Ten participants were recruited with ages ranging from 24 to 61 years. Participants had intradermal Indocyanine Green injections administrated between left finger digits. Fluorescence was imaged for 5 min sequences with an infra-red camera prior to lymph vessel load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…shows the lymphatic behaviour varied at baseline, with normative values similar to that in the published literature[19][20].…”
supporting
confidence: 78%
See 2 more Smart Citations
“…shows the lymphatic behaviour varied at baseline, with normative values similar to that in the published literature[19][20].…”
supporting
confidence: 78%
“…Lymphatic activity was characterised using a standardized technique involving near-infrared fluorescence lymphatic imaging (NIRFLI). An Indocyanine Green (ICG) contrast agent was injected to help visualise dermal lymphatic vessels [19][20]. To review briefly, ICG was diluted in a saline solution to achieve the required dose for testing (50μL, 0.05% w/v).…”
Section: Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 In ammatory mediators 48 secreted from damaged and nearby immune cells lead to progressive in ammatory oedema, which increases interstitial pressures, the mechanical distortions of cells and tissues, and the growing obstructions within the vasculature and lymphatics. 49 Damage may be ampli ed in ischaemic tissue after reperfusion through the release of reactive oxygen species (ROS), termed reperfusion injury.…”
Section: Distorting Effect Of Frictionmentioning
confidence: 99%
“…However, this approach does not account for the damage mechanisms associated with the majority of PUs involving small tissue strains in superficial dermal tissues. Indeed, in this case, researchers have used biophysical and imaging techniques to assess the response of superficial skin tissues under representative loads 12–15 . These studies revealed that due to microvascular compromise, tissue ischemia can occur in both able‐bodied and patient cohorts during periods of lying and sitting postures.…”
Section: Introductionmentioning
confidence: 99%